2016
DOI: 10.4085/1062-6050-51.6.03
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Injury Incidences in Male Professional Adult and Elite Youth Soccer Players: A Systematic Review

Abstract: Context: The incidence of injury for elite youth and professional adult soccer players is an important concern, but the risk factors for these groups are different.Objective: To summarize and compare the injury incidences and injury characteristics of male professional adult and elite youth soccer players.Data Sources: We searched MEDLINE and Web of Science using the search terms elite, international, European, soccer, football, injury, injuries, epidemiology, incidence, prevalence, not female, not American fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
233
3
22

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(266 citation statements)
references
References 56 publications
8
233
3
22
Order By: Relevance
“…Research conducted among young football players showed that almost 40% of football players playing at various game levels had non-mechanical injuries in lower limbs [14]. Most of them involve hamstrings strains, traumas of the tendons and ligaments of the knees [15][16][17][18]. Moreover Ekstrand et al [19] conducted research among 23 football teams in which they stated that, the possibility of injury is around 8 per 1000 hours of play, especially in competitive matches.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted among young football players showed that almost 40% of football players playing at various game levels had non-mechanical injuries in lower limbs [14]. Most of them involve hamstrings strains, traumas of the tendons and ligaments of the knees [15][16][17][18]. Moreover Ekstrand et al [19] conducted research among 23 football teams in which they stated that, the possibility of injury is around 8 per 1000 hours of play, especially in competitive matches.…”
Section: Introductionmentioning
confidence: 99%
“…To date, injury prevention in these professional youth players has received very little research attention (O'Brien & Finch, ), despite knowledge that physiological loads, psychological loads, and injury rates are very high in these settings (Price et al., ; Brink et al., ). Reported injury incidences in this population range from 2.0 to 19.4 injuries per 1000 hours, with a recent systematic review finding a higher incidence of training injuries in professional youth players, compared to their adult counterparts (Pfirrmann et al., ). In comparison, the reported injury rate in amateur male soccer players ranges from 0.8 to 8.5 injuries per 1000 hours (Junge et al., ; Owoeye et al., ).…”
mentioning
confidence: 96%
“…The majority (79%) of respondents answered that they felt sharing/using their academy's injury data for academic research was worthwhile and important. This is somewhat at odds with the scarcity of epidemiological studies in elite youth football within the scientific literature (Pfirrmann et al 2016). However, that so many applied practitioners believe that collaborating with academic researchers is of value bodes well for future investigations.…”
Section: Perceived Valuementioning
confidence: 99%
“…Indeed, a wealth of evidence exists detailing the epidemiology of footballrelated injury among senior professional players, most notably via the series of Union of European Football Associations (UEFA) elite club injury studies (Ekstrand et al 2011;Ueblacker et al 2015;Ekstrand et al 2016). However, a recent systematic review investigating injury epidemiology within elite youth football identified only six studies meeting the inclusion criteria (injury and exposure data collected prospectively over the course of at least six months among high-level players aged between eight and 19 years of age), with only two of these published in the last 10 years (Pfirrmann et al 2016). The paucity of descriptive injury data relevant to professional club academy football players is perhaps surprising given the prevalence of such institutions (Richardson et al 2004).…”
Section: Introductionmentioning
confidence: 99%